RETHINKING THE “ONE CHINA POLICY”: A PATH TO RATIONAL REUNIFICATION - Mutia Hariati Hussin; Andini Hayu Agus Putri; Tulus Warsito (Jurnal Dinamika Global, 2025)
This study re-examines the "One China Policy" by analyzing the potential for China-Taiwan reunification through a non-military framework. Based on the "Unification through Systemic Evolution and Integration" model, this paper argues that China is systematically implementing a gradual strategy to achieve unification without military coercion. This strategy rests on three main pillars. First, comprehensive economic integration has created massive dependence, with China absorbing over 40% of Taiwan's exports, supported by legal frameworks such as the ECFA. Second, a "lawfare" approach and social integration through policies such as the "31 Measures," aimed to erode the boundaries of sovereignty by integrating Taiwanese individuals and entities into China's system. Third, socio-cultural integration is being promoted through an "integrated development demonstration zone" in Fujian, aimed at building "emotional bonds" and "spiritual ties." Although this scheme is designed to make reunification a pragmatic choice, its success is severely limited by the strong democratic identity of the Taiwanese people, who reject the "One Country, Two Systems" model, and the balancing role of the United States.